Enhancing Thermal Stability of Hybrid-Modified Local Asphalt - Khalaf, Riyam H.; Abed, Mohammed A. (Al-Nahrain Journal for Engineering Sciences, 2025)
Chemical additives and polymeric materials, selected for their compatibility and ability to improve asphalt's performance in demanding environments. Key additives, including Polyphosphoric Acid (PPA), Polyvinyl Acetate (PVAC) beads, Maleic Anhydride (MA), and Ethylene Vinyl Acetate (EVA) resin, were mixed in precise ratios with the asphalt binder. These additives were chosen to evaluate their effects on crucial performance indicators, such as the Penetration Index (PI) and activation energy, which measure the material’s thermal stability, flexibility, and resistance to deformation. Results demonstrated that the addition of these materials significantly increased the asphalt’s activation energy by up to 45.44%, enhancing its resistance to temperature fluctuations and providing better stability under various environmental stresses. The Penetration Index (PI) also improved notably, indicating that modified asphalt exhibits greater durability and reduced susceptibility to cracking or deformation under thermal changes. These enhancements contribute to lower road maintenance requirements and support greater energy efficiency in asphalt production and application processes. Compared to neat asphalt, the modified asphalt exhibited superior thermal stability, mechanical resilience, and overall performance, making it suitable for use in diverse climatic conditions. This study provides valuable insights into sustainable asphalt modification techniques, emphasizing the role of polymer and chemical additives in extending pavement lifespan and reducing environmental impact through improved material properties.